2016 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM) 2016
DOI: 10.1109/asonam.2016.7752235
|View full text |Cite
|
Sign up to set email alerts
|

Detecting malicious campaigns in crowdsourcing platforms

Abstract: Crowdsourcing systems enable new opportunities for requesters with limited funds to accomplish various tasks using human computation. However, the power of human computation is abused by malicious requesters who create malicious campaigns to manipulate information in web systems such as social networking sites, online review sites, and search engines. To mitigate the impact and reach of these malicious campaigns to targeted sites, we propose and evaluate a machine learning based classification approach for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The small dataset consists of 23,220 crowdsourcing campaigns with manually labeled information (i.e., which campaign is malicious or legitimate), including 3,356,153 tasks 3 . This dataset was collected from MTurk, Microworkers, Rapidworkers, and Shorttask by using a crawler that we developed for the prior work [1]. The crawler collected 23,220 campaigns, including detailed campaign descriptions within a period of three months between November 2014 and January 2015.…”
Section: Datasets and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The small dataset consists of 23,220 crowdsourcing campaigns with manually labeled information (i.e., which campaign is malicious or legitimate), including 3,356,153 tasks 3 . This dataset was collected from MTurk, Microworkers, Rapidworkers, and Shorttask by using a crawler that we developed for the prior work [1]. The crawler collected 23,220 campaigns, including detailed campaign descriptions within a period of three months between November 2014 and January 2015.…”
Section: Datasets and Methodologymentioning
confidence: 99%
“…On another note, Fayazi et al [3] showed that malicious requestors targeted popular search engines (e.g., Google, Bing), social media sites (e.g., Facebook, Pinterest), and online e-commerce sites (e.g., Amazon) by creating malicious tasks and hiring workers from crowdsourcing platforms. Choi et al [1] proposed a novel approach to define, classify and detect malicious campaigns that exist on several popular crowdsourcing platforms. They first analyzed the characteristics of malicious campaigns as opposed to legitimate campaigns, and then made use of these characteristics (or features) to build a classification model to identify malicious campaigns with a high accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations